Buying, behaving, and being: A portrait of contemporary tourists - Decrop, A.; Woodside, Arch (2017)
© 2017 by Emerald Publishing Limited. The Consumer Psychology of Tourism, Hospitality, and Leisure (CPTHL) Symposium, launched 17 years ago, has been the first conference to develop a strong focus on consumer behavior in the field of tourism and leisure from both theoretical and practical perspectives. After a series of eight successful symposia held throughout the World (from Hawaii to Vienna, from Montreal to Istanbul), the Center for Research on Consumption and Leisure (CeRCLe) within the University of Namur has hosted the event in July 2015. This book features a selection of the best papers that have been presented during the symposium plus two additional papers that complement and extend the theme of this volume. The core focus of this volume is on describing and interpreting contemporary tourists and their behaviors: buying behaving, and being tourists.